Variety shows in the Chinese market: applying uses and gratifications theory and culture theory and to understand audiences’ viewer engagement, motivations and preferences - Lin, Zhixian (Kansas State University, 2020)
As variety shows are rapidly developing in the Chinese market, brand-new viewer engagement is occurring in the young generation of China. This study applies uses and gratifications theory to understand the motivation and viewer engagement of Chinese audiences. With the development of technology, variety shows break free from cable television; the combination of online players provides audiences a broader platform to consume different styles of variety shows. Thus, this study applies uses and gratifications theory to examine the satisfaction that technology provides to viewers, as well as culture theory as another theory to understand whether cultural orientation has impacts on consuming variety shows.
Keywords: Variety shows; Uses and gratifications; Culture theory; Chinese audiences